HUBUNGAN ANTARA MUTU PELAYANAN DENGAN KESETIAAN PASIEN ( SURVEY PADA PASIEN BAGIAN JANTUNG RUMAH SAKIT INTERNASIONAL BINTARO ) - Henry Eryanto (Fakultas Ekonomi Universitas Negeri Jakarta, 2011)
ABSTRACT This research was aimed at describing connections between : 1) The Quality of Services to the Patient Loyalty, 2)The Satisfaction to the Patient Loyalty, 3) The Quality of Services and Patients Satisfaction, all together, to the patient loyalty. This study was held in the Bintaro International Hospital, Tangerang. The method of research is survey method. The population consist of all internal disease patients of Bintaro International Hospital, Tangerang. Sample of research are 40 patients which were taken by random sampling method. The result of research, that the service quality and the patient satisfaction themselves or all together, giving significant result toward the patient loyalty. The attitude towards the improvement quality of service, and patient satisfaction need to be trained for the employees of Bintaro International Hospital. This matter cannot be separated from the employees recruitment. Spesifically for the best services for their patients, beside that matters the hospital management must be improved their tools and equipment that they’re used, and would be hold the trainings for their employees.Keywords: Quality of Service, Satisfaction, Loyalty.